Efeito do treinamento de força realizado com duração de repetição controlada e auto-selecionada na força e massa muscular de homens jovens - Chaves, Talisson Santos (Universidade Federal de São Carlos, 2018)
The aim of the study was to compare the effect of RD SELF, with and without total training volume equalized with RD CON, on muscle strength and hypertrophy. Twenty healthy untrained university students were recruited for this study. An intra-subject design was used in which the each participant’s leg was allocated in a randomized and balanced way: (1) Control RD (CON); (2) Self-selected RD with equalized volume (SELF-EV); Self-selected RD without equalized volume (SELF). All RT protocols were performed unilaterally using a conventional leg-extension machine, twice a week for 8 weeks. For the SELF and CON protocols, the participants performed 3 sets for muscle failure at 70% 1-RM, and 2 minutes rest period was granted between sets for both protocols. During SELF-EV, the same intensity and between-sets rest intervals were utilized, however, the number of sets varied (2-3 sets) due to TTV equalization with the CON group. Significant differences were found for TTV between protocols over 8 weeks (P = 0.0009), with SELF resulting in higher TTV compared to CON and SELF-EV. However, all training protocols showed significant increases in strength (P <0.0001) and muscle AST (P <0.0001), with no significant differences between groups (P> 0.05). In conclusion, resistance training with SELF RD, regardless of VTT, was equally effective in inducing increases in strength gains and muscle hypertrophy compared to RD controlled.
Effect of resistance training performed with controlled and self-selected repetition duration on strength and muscle mass in young men's
Keywords: Duração de repetição; Repetition duration; Treinamento de força; Resistance training; Hipertrofia muscular; Muscle hypertrophy; Força máxima; Maximal strength; CIENCIAS BIOLOGICAS::FISIOLOGIA